2008
DOI: 10.1163/157181808x301809
|View full text |Cite
|
Sign up to set email alerts
|

"It's Like Mental Torture": Participation and Mental Health Services

Abstract: This article discusses findings from an ethnographic research study looking at the ways in which children's participation rights are incorporated within an adolescent mental health inpatient unit. The practitioners working within this setting have reinterpreted the concept of 'participation' to suit a coercive agenda associated with the authoritarian medical model of treatment used within child psychiatry. Indeed, the use of the term 'participation' has become a tool to enforce children's compliance with adult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
74
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(75 citation statements)
references
References 11 publications
(20 reference statements)
0
74
0
1
Order By: Relevance
“…Finally, all studies but one (Molesworth & Crome, ) presented findings in a comprehensive manner providing quotes illustrating the main themes obtained by the analysis. Nonetheless, several studies did not provide sufficient detail on issues such as justification of the research design ( n = 3; Iachini, Hock, Thomas, & Clone, ; Molesworth & Crome, ; Street, ), recruitment strategy ( n = 6; Lee et al, ; LeFrançois, ; Ma & Lai, ; Molesworth & Crome, ; Offord, Turner, & Cooper, ; Street, ), data collection ( n = 3; LeFrançois, ; Molesworth & Crome, ; Street, ), the relationship between researcher and participants ( n = 14; Buckley et al, ; Harper, Dickson, & Bramwell, ; Hart, Saunders, & Thomas, ; Iachini et al, ; Kovshoff et al, ; Lee et al, ; LeFrançois, ; Molesworth & Crome, ; Offord et al, ; Oruche, Downs, Holloway, Draucker, & Aalsma, ; Pelto‐Piri, Engstrom, K., & Engstrom, ; Street, ; Tam‐Seto & Versnel, ; Wisdom, Clarke, & Green, ), ethical issues ( n = 4; Abrines‐Jaume et al, ; LeFrançois, ; Molesworth & Crome, ; Wisdom et al, ) and rigour of data analysis ( n = 4; Hart et al, ; LeFrançois, ; Molesworth & Crome, ; Street, ). Finally, contribution to research, knowledge or policy was not discussed in two studies (Molesworth & Crome, ; Street, ), new areas of research were not identified in six studies (Buckley et al, ; Hart et al, ; Lee et al, ; Molesworth & Crome, ; Pycroft, Wallis, Bigg, & Webster, ; Street, ) and generalizability of findings was not taken into account in nine studies (Buckley et al, ; Bury, Raval, & Lyon, ; Coyne et al, ; Kovshoff et al, ; LeFrançois, ; Molesworth & Crome, ; Offord et al, ; Pelto‐Piri et al, ; Street, …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, all studies but one (Molesworth & Crome, ) presented findings in a comprehensive manner providing quotes illustrating the main themes obtained by the analysis. Nonetheless, several studies did not provide sufficient detail on issues such as justification of the research design ( n = 3; Iachini, Hock, Thomas, & Clone, ; Molesworth & Crome, ; Street, ), recruitment strategy ( n = 6; Lee et al, ; LeFrançois, ; Ma & Lai, ; Molesworth & Crome, ; Offord, Turner, & Cooper, ; Street, ), data collection ( n = 3; LeFrançois, ; Molesworth & Crome, ; Street, ), the relationship between researcher and participants ( n = 14; Buckley et al, ; Harper, Dickson, & Bramwell, ; Hart, Saunders, & Thomas, ; Iachini et al, ; Kovshoff et al, ; Lee et al, ; LeFrançois, ; Molesworth & Crome, ; Offord et al, ; Oruche, Downs, Holloway, Draucker, & Aalsma, ; Pelto‐Piri, Engstrom, K., & Engstrom, ; Street, ; Tam‐Seto & Versnel, ; Wisdom, Clarke, & Green, ), ethical issues ( n = 4; Abrines‐Jaume et al, ; LeFrançois, ; Molesworth & Crome, ; Wisdom et al, ) and rigour of data analysis ( n = 4; Hart et al, ; LeFrançois, ; Molesworth & Crome, ; Street, ). Finally, contribution to research, knowledge or policy was not discussed in two studies (Molesworth & Crome, ; Street, ), new areas of research were not identified in six studies (Buckley et al, ; Hart et al, ; Lee et al, ; Molesworth & Crome, ; Pycroft, Wallis, Bigg, & Webster, ; Street, ) and generalizability of findings was not taken into account in nine studies (Buckley et al, ; Bury, Raval, & Lyon, ; Coyne et al, ; Kovshoff et al, ; LeFrançois, ; Molesworth & Crome, ; Offord et al, ; Pelto‐Piri et al, ; Street, …”
Section: Resultsmentioning
confidence: 99%
“…Notably, there were three studies that suffered from poor reporting across most items from the Critical Appraisal Skills Programme tool (Critical Appraisal Skills Programme, ), related to recruitment strategy, data collection or rigour of the analysis (LeFrançois, ; Molesworth & Crome, ; Street, ). Moreover, one study used open‐ended survey questions to explore experiences of youth receiving mental health services, which appeared to be a highly flawed data collection method (Lee et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies report on both foster care and residential care (e.g., Munford & Sanders, 2015;Polvere, 2014), or a combination of day-patient and inpatient residential care (LeFrançois, 2008). Some studies report on both foster care and residential care (e.g., Munford & Sanders, 2015;Polvere, 2014), or a combination of day-patient and inpatient residential care (LeFrançois, 2008).…”
Section: Exclusion Criteriamentioning
confidence: 99%
“…Several studies do report on indirect effects of participation during residential care in terms of young people's experiences related to the (lack) of participation (Fudge Schormans & Rooke, 2008;Hepper et al, 2005;Roesch-March, 2014), such as distressing feelings and passiveness due to lack of participation (see also LeFrançois, 2008;Polvere, 2014). Several studies do report on indirect effects of participation during residential care in terms of young people's experiences related to the (lack) of participation (Fudge Schormans & Rooke, 2008;Hepper et al, 2005;Roesch-March, 2014), such as distressing feelings and passiveness due to lack of participation (see also LeFrançois, 2008;Polvere, 2014).…”
Section: Participation and Outcomesmentioning
confidence: 99%